Lung injury following a 50-metre fall into water. Issue 2 (April 1978) - Robertson, H T; Lakshminarayan, S; Hudson, L D
Abstract : The pulmonary complications of a 50-metre fall to the water (a form of suicide attempt producing 87% mortality) were studied in 15 survivors. Presenting findings included crackles, haemoptysis, and hypotension. The alveolar-arterial oxygen difference was greater than 150 mmHg (20 kPa) in nine subjects on admission. Ventilatory failure developed in 10 of the patients, including all of those with massive haemoptysis. Radiographic findings included pneumothorax and diffuse pulmonary opacities adjacent to the area of impact. Pneumothorax developed within 12 hours of admission in 10 of 15 subjects but was associated with rib fractures in only four subjects. The clinical course of the condition is consistent with the hypothesis that the traumatic pulmonary tears produced interstitial emphysema, with subsequent development of pneumomediastinum, subcutaneous emphysema, and pneumothorax. Pneumothorax is a common complication of severe lung contusion even in the absence of penetrating pleural injury.